Analysis of Learning Media Development Needs Exe Learning Straight Motion Material Changes Regularly for Senior High School Class XI - Novela, Erma (IJOEM Indonesian Journal of E-learning and Multimedia, 2023)
The purpose of the study entitled Needs Analysis of Learning Media Development Exe Learning Straight Motion Material Changes Regularly for Senior High School Class XI is to conduct a needs analysis to find out how much students and teachers need to develop E-module learning media based on the Exe learning application on Straight Motion Changing Regular Class XI material. The method used is the qualitative descriptive method. Data collection techniques carried out in this study were carried out by observation and interview activities. The instruments used are the observation data collection technique using an observation sheet instrument and when the interview data collection technique uses an instrument, namely an interview sheet consisting of teacher interview sheets and student interview sheets. From the research conducted, it was found that the understanding of student concepts at SMA Negeri 1 Kota Bengkulu, SMA Negeri 3 Kota Bengkulu, and SMA Negeri 9 Kota Bengkulu still needs to be improved, especially in the subject of physics of Straight Motion Changing Regular material. This is due to learning media that is still not interesting. Based on the results of the needs analysis conducted for the development of E-modules for Class XI Physics Regular Changing Straight Motion material, it can be concluded that teachers and students at SMA Negeri 1 Kota Bengkulu, SMA Negeri 3 Kota Bengkulu, and SMA Negeri 9 Kota Bengkulu still need the development of E-modules to improve students' understanding of concepts.